Comparative antibiogram analysis of bacterial isolates from mastitic milk of cattle and buffalo in Haryana - Rahul Yadav; Pankaj Kumar; Anand Prakash; Bhanot, Vandna (Indian Journal of Dairy Science, 2024)
Mastitis causes huge economic losses to dairy industries worldwide. It is caused by various microorganisms, of which bacterial etiology is primarily important. Both Gram-positive and Gram-negative bacteria are involved in causation of disease. In the present study, 8561 milk samples from both cattle and buffalo combined were tested and occurrence of mastitis was recorded in 72.73 % (n = 6227/8561) milk samples. Occurrence of mastitis was non–significantly (p>0.05) higher in cattle (86.31%) than buffaloes (66.97%). California Mastitis Test (CMT) showed significantly (p